Pengaruh Mutu Pelayanan Kesehatan Terhadap Kepuasan Pasien Di Klinik Pratama Asy Syifa Kota Bengkulu - Suciati, Ike; Oktavidiati, Eva; Febriawati, Henni; Kosvianti, Emi (Avicenna: Jurnal Ilmiah, 2024)
Background: The quality of clinical services is very important, patient satisfaction is influenced by the quality of health services provided. The aim of the research is to determine the influence of health service quality on Prolanis patient satisfaction using the servqual (service quality) model. Method : the research uses quantitative methods through a cross sectional approach, namely the research design aims to determine the influence of the relationship between the independent variable and the dependent variable at the same time. Results : The research results show that the characteristics of the largest respondents were >50 years old, 60 respondents, 57 respondents were female, and 43 respondents worked as ASN. There is a significant influence between tangible and patient satisfaction of Prolanis participants in the Good category of 69.7%, Reliability and patient satisfaction of Prolanis participants in the Good category of 70.2%, Responsivennes and patient satisfaction of Prolanis participants in the Good category of 69.8%, Assurance with patient satisfaction of Prolanis participants in the Good category was 66.7%, Emphaty with patient satisfaction of Prolanis participants in the Good category was 67.7%. Conclusion : There is a significant influence between tangible and patient satisfaction of Prolanis participants who received promotive and preventive activity programs in the Good category at the Pratama Asy Syifa Clinic, Bengkulu City.   Keywords : Quality of Health Services, Patient Satisfaction